(untitled) (Research, Society and Development, 2021)
The objective of this work was to determine whether preventive consumption of a homeopathic product via drinking water would protect mouse kidneys from a challenge with the nephrotoxic antibiotic gentamicin. We used 40 Swiss mice divided into four groups with ten animals each. The homeopathic product was supplied through water for 30 days in a preventive manner and gentamicin for 10 days to induce an experimental renal failure. The groups were as follows: Negative-CT (homeopathic and gentamicin was not provided), Positive-CT (did not receive homeopathic, but received gentamicin 40 mg/kg), T2 (received 0.002 ml of the product per animal/day, and received gentamicin 40 mg/kg), and T4 (0.004 ml of the product per animal/day and received gentamicin 40 mg/kg). On days 12 and 20, blood and tissue samples were collected from five animals in each group. No histopathological lesions were found in mouse kidneys. However, levels of thiobarbituric acid reactive substances, reactive oxygen species, and nitrite/nitrate ratios in the kidney of the Positive-CT group were higher compared to the other groups. As for glutathione S-transferase, on the 20th day, the groups that used the homeopathic product (T2 and T4) had higher activities than the positive TC. Therefore, the results suggest that prophylactic consumption of the hepatoprotective homeopathic product can decrease lipid peroxidation, nitrous stress, and oxidative stress at the renal level when consecutive doses of gentamicin induce insufficiency.